Analysis of Consumer Behavior Toward Increased Sales of Orgamas Liquid Organic Fertilizer Products - Budi Utomo; Steffan Albert (Agricultural Science, 2020)
This study aims to determine: 1. Knowing the response and interest of farmers to the products of Organic Liquid Organic Fertilizer Orgamas in the Dawarblandong area. 2. Knowing the cause and effect of farmers in buying Orgamas Liquid Organic Fertilizer products. 3. Develop strategies to increase sales of Orgamas Liquid Organic Fertilizer products. Results of the study: 1. Farmers in Dawarblandong have a high level of expectation for organic fertilizer products that can help increase their productivity, but these expectations are limited by cultural factors so that farmers give the highest value to the attribute of excellence and the lowest value to the availability attribute of liquid organic fertilizer. Orgamas. 2. Farmers have different interpretations of the attributes inherent in the Orgamas Liquid Organic Fertilizer product, they assess that the attributes of excellence, price, and delivery are able to shape their interest in buying and using Orgamas Liquid Organic Fertilizer, but not the availability, familiarity and brand attributes. . 3. Based on the SWOT analysis concluded by the Cartesian Graph, Intan Abatani's management is facing various internal threats and weaknesses, so Intan Abatani's management needs to develop an alternative strategy in the form of a SWOT Matrix design to create a plan to save the company from large losses.